2020
DOI: 10.3389/fpsyg.2020.604004
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Alexithymia in Post-surgery. Differences on Body Image and Psychological Adjustment in Breast Cancer Patients

Abstract: Breast cancer is a disease that is difficult to face and that often hinders body acceptance. Body changes due to surgery can be very emotionally challenging for those who experience them. The aim of this study is to explore the differences on body image and psychological adjustment on women with breast cancer with high and low alexithymia according to the type of surgery. In this cross-sectional study, 119 women diagnosed with breast cancer (stages I, II, and III) were evaluated with different self-report ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…The type of surgery performed as part of the treatment does not indicate significant results, although the MBI analysis shows that women undergoing conservative surgery have 43.7% beneficial chances on the anxiety scale, and 55.6% trivial effect. These results are consistent with other studies indicating that women undergoing MST reported worse body image, greater pain, higher depression, higher anxiety and hopelessness scores than women undergoing BCT [14,15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The type of surgery performed as part of the treatment does not indicate significant results, although the MBI analysis shows that women undergoing conservative surgery have 43.7% beneficial chances on the anxiety scale, and 55.6% trivial effect. These results are consistent with other studies indicating that women undergoing MST reported worse body image, greater pain, higher depression, higher anxiety and hopelessness scores than women undergoing BCT [14,15].…”
Section: Discussionsupporting
confidence: 92%
“…This option is the used when women want to preserve their body image. Women who had MST showed the greatest difficulties in understanding their own emotions [14].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency to focus thinking towards concrete situations is related to the confrontation that these women activate during their treatment, focusing on the avoidance of situations that cause them to suffer [34][35]. These data address some of the limitations found in previous studies, such as that proposed by Gritti et al [23] and Gutiérrez et al [33], in which conclusive results on the di culty of emotional identi cation in the active phase of treatment was found.…”
Section: Discussionsupporting
confidence: 74%
“…The present review observed that women face several issues, including choosing the right undergarment and appearance of chest. 14,16,23,24 Qualitative research done in this aspect on women who have undergone mastectomy has shown that the surgery adversely affects women. The research clearly showed that women miss their self-image and hence their body appearance due to mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, coping in these women was directly associated with their body image and subsequent psychological adaptation for the same. 23 Body image issues are further augmented by the fact that women post-mastectomy have issues in finding right undergarments for use. This is one of the factors that makes it difficult for women post-mastectomy to socially adapt in society.…”
Section: Body Image Issues and Coping Post-mastectomymentioning
confidence: 99%